Loteprednol etabonate (submicron) ophthalmic gel 0.38% dosed three times daily following cataract surgery: integrated analysis of two Phase III clinical studies - Fong R (Dove Medical Press, 2019)
Raymond Fong,1 Megan E Cavet,2 Heleen H DeCory,2 Jason L Vittitow31Manhattan Eye, Ear and Throat Hospital and Lenox Hill Hospital, New York, NY, USA; 2Medical Affairs, Bausch + Lomb, Rochester, NY, USA; 3Clinical Affairs, Bausch + Lomb, Bridgewater, NJ, USAPurpose: To evaluate the efficacy and safety of a submicron formulation of loteprednol etabonate (LE) gel 0.38% instilled three times daily (TID) compared with vehicle for the treatment of inflammation and pain following cataract surgery with intraocular lens implantation, integrated across two multicenter, double-masked, randomized, parallel-group, Phase III studies.Patients and methods: Subjects ≥18 years of age with anterior chamber (AC) cells ≥grade 2 (6–15 cells) on day 1 after cataract surgery were randomized to receive 1 drop of LE gel 0.38% TID, twice daily (not reported/analyzed herein), or vehicle instilled in the study eye for 14 days. Primary endpoints were the proportion of subjects with resolution of AC cells and grade 0 (no) pain at postoperative day 8. Safety outcomes included adverse events (AEs), ocular signs, fundoscopy results, visual acuity, intraocular pressure (IOP), and tolerability (drop comfort and ocular symptoms).Results: The integrated intent-to-treat population included 742 subjects (LE gel 0.38% TID, n=371; vehicle, n=371). Significantly more subjects in the LE gel 0.38% TID group compared with the vehicle group had complete resolution of AC cells (29.6% vs 15.1%) and grade 0 pain (74.4% vs 48.8%) at day 8 (P<0.0001 for both). LE gel 0.38% TID was safe and well tolerated, with only 1 LE-treated subject experiencing an IOP elevation ≥10 mm Hg. Most treatment-related AEs were mild and occurred less frequently with LE gel 0.38% than with vehicle. The majority (>75%) of subjects in each treatment group reported no drop discomfort. There were no reports of blurred vision with LE gel.Conclusion: The results of this integrated analysis indicate that LE (submicron) gel 0.38% administered TID is safe and effective for the treatment of ocular inflammation and pain following cataract surgery, with minimal risk of IOP elevation.Keywords: cataract surgery, postoperative pain, postoperative inflammation, loteprednol etabonate, submicron, integrated analysis